Room-Temperature Triethylamine Sensor Based on Reduced Graphene Oxide/CeO2 Nanocomposites - Zito, Cecilia A. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Volanti, Diogo P. [UNESP] (American Chemical Society (ACS), 2023)
Triethylamine (TEA) detection has been widely performed by using chemoresistive sensors. Nevertheless, chemoresistive sensors still exhibit limitations to be addressed in terms of power consumption and humidity interference, and developing efficient TEA sensors operated at low temperatures and humid conditions remains a challenge. Here, we present the effect of reduced graphene oxide (RGO) on the TEA-sensing performance of CeO2 nanospheres at room temperature and a relative humidity (RH) range of 34-70%. We show that CeO2 is a suitable sensing material for TEA detection at room temperature and humidity conditions; however, the modification with RGO greatly improves the TEA-sensing performance. The RGO/CeO2 nanocomposite has higher sensitivity and selectivity to TEA than the bare CeO2-based sensor, in addition to the low theoretical detection limit of 1 ppm at 70% RH. Moreover, we elucidate that humidity plays a positive role in the detection of TEA. Our findings elucidate that RGO positively affects the sensing performance of CeO2 nanospheres, which can be attributed to the improvements in the baseline electrical resistance and enhancement of the active sites for TEA adsorption due to the RGO modification. This work provides a promising strategy for developing sensitive TEA sensors with practical applications.
Keywords: ceria; cerium dioxide; chemoresistive; humidity; microwave-assisted synthesis; volatile organic compounds